In vitro antibacterial activity of ZnO and Nd doped ZnO nanoparticles against ESBL producing Escherichia coli and Klebsiella pneumoniae - Abdulrahman Syedahamed Haja Hameed; Chandrasekaran Karthikeyan; Abdulazees Parveez Ahamed; Nooruddin Thajuddin; Naiyf S. Alharbi; Sulaiman Ali Alharbi; Ganasan Ravi (Scientific Reports)
Abstract Pure ZnO and Neodymium (Nd) doped ZnO nanoparticles (NPs) were synthesized by the co-precipitation method. The synthesized nanoparticles retained the wurtzite hexagonal structure. From FESEM studies, ZnO and Nd doped ZnO NPs showed nanorod and nanoflower like morphology respectively. The FT-IR spectra confirmed the Zn-O stretching bands at 422 and 451 cm−1 for ZnO and Nd doped ZnO NPs respectively. From the UV-VIS spectroscopic measurement, the excitonic peaks were found around 373 nm and 380 nm for the respective samples. The photoluminescence measurements revealed that the broad emission was composed of ten different bands due to zinc vacancies, oxygen vacancies and surface defects. The antibacterial studies performed against extended spectrum β-lactamases (ESBLs) producing strains of Escherichia coli and Klebsiella pneumoniae showed that the Nd doped ZnO NPs possessed a greater antibacterial effect than the pure ZnO NPs. From confocal laser scanning microscopic (CLSM) analysis, the apoptotic nature of the cells was confirmed by the cell shrinkage, disorganization of cell wall and cell membrane and dead cell of the bacteria. SEM analysis revealed the existence of bacterial loss of viability due to an impairment of cell membrane integrity, which was highly consistent with the damage of cell walls.